The China Society Yearbook, Volume 5 - Ru, Xin; Lu, Xueyi; Li, Peilin (The Chinese Academy of Social Sciences Yearbooks: Society, 2011)
The China Society Yearbook, Volume 5 continues the ten-year tradition of presenting precise and venerable academic principles by compiling the findings of the Chinese Academy of Social Sciences' subject research group for the "Analysis and Forecast of the Social Situation".